A Multi band mini printed omni directional antenna with v-shaped for RFID applications - Evizal; Tharek, Abd. Rahman, Prof. Dr.; Shahrul Kamal, Abd Rahim, Prof. Madya Dr. Ir.; Mohd Faizal, Jamlos, Dr. (EMW Publishing, 2011)
Link to publisher's homepage at http://emacademy.org/emwave/